Comparison of free thyroxine measurement by chemiluminescence and equilibrium dialysis following 131I therapy in hyperthyroid cats. Issue 12 (December 2020) - Stammeleer, Lisa; Buresova, Eva; Stock, Emmelie; Feenstra, Laurien; Vandermeulen, Eva; Duchateau, Luc; Van de Maele, Isabel; Daminet, Sylvie
Objectives: The first objective was to assess correlation between free thyroxine (fT4) measurements by equilibrium dialysis (fT4ED; Antech Diagnostics) and a chemiluminescent enzyme immunoassay (fT4CEIA; IMMULITE 2000 Veterinary Free T4 [Siemens Healthcare Diagnostics Products]) in hyperthyroid, otherwise healthy, cats before (T0), and 1 month (T1) and 11–23 months (T2) after radioactive iodine ( 131 I) therapy. The second objective was to determine correlation between thyroid status based on fT4 (by both techniques) and the gold standard, thyroid scintigraphy. Methods: Thyroid status, including thyroid-stimulating hormone (TSH), total thyroxine (TT4) and fT4 serum concentrations, were assessed in 45 client-owned hyperthyroid cats before (T0), and 1 month (T1) and 11–23 months (T2) after 131 I therapy. fT4 was determined by a chemiluminescent enzyme immunoassay (CEIA) and equilibrium dialysis (ED). Quantitative thyroid scintigraphy (with sodium 99m-Tc-pertechnetate) was performed at T2. Results: Spearman correlation between fT4CEIA and fT4ED was 0.81, 0.88 and 0.79 at T0, T1 and T2, respectively. fT4CEIA was consistently lower than fT4ED, with a median difference of −5.4 pmol/l ( P <0.001) and −4.9 pmol/l ( P <0.0001) at T1 and T2, respectively. At T2, all cats were identified as euthyroid based on thyroid scintigraphy. None of the cats were identified as being hypothyroid, based on serum TT4 and TSH measurements. Nine of 22 (40.9%) cats had an fT4CEIA below the reference interval (RI) at T2, whereas only 2/22 (9.1%) cats had an fT4ED concentration below the RI at T2. Conclusions and relevance: Good correlation exists between both assays at T1 and T2, but a significant systematic difference is noted at both time points. This could be an indication for reconsideration of the current RI, although further studies are warranted for assessing test accuracy (in otherwise healthy cats and cats with non-thyroidal illness). At this time, routine use of fT4CEIA after 131 I therapy is not advised in feline patients.